2020
DOI: 10.1002/mnfr.201901274
|View full text |Cite
|
Sign up to set email alerts
|

Gluten‐Free Diet in IBD: Time for a Recommendation?

Abstract: Patients and providers alike are highly interested in identifying potentially useful dietary interventions in the management of inflammatory bowel diseases (IBD). This review examines the clinical associations of celiac disease (CeD), non‐celiac gluten sensitivity (NCGS), and IBD with a focus on available data of the therapeutic efficacy of gluten‐free diet (GFD) or low‐gluten‐containing diets in the therapy of IBD. There is a strong association between CeD and microscopic colitis, but the prevalence of CeD am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 57 publications
(131 reference statements)
0
35
0
Order By: Relevance
“…The authors confirmed that a trial GFD in IBD patients with significant gastrointestinal symptoms may be a safe treatment option, but advised that further prospective studies are needed to understand the mechanism of gluten sensitivity in IBD [24]. In a Swiss IBD cohort, no differences in terms of disease activity, hospitalization and surgery were found in patients consuming or not consuming gluten [25]. Therefore, there is not yet enough evidence to recommend a GFD for IBD patients.…”
Section: Gluten Free Dietmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors confirmed that a trial GFD in IBD patients with significant gastrointestinal symptoms may be a safe treatment option, but advised that further prospective studies are needed to understand the mechanism of gluten sensitivity in IBD [24]. In a Swiss IBD cohort, no differences in terms of disease activity, hospitalization and surgery were found in patients consuming or not consuming gluten [25]. Therefore, there is not yet enough evidence to recommend a GFD for IBD patients.…”
Section: Gluten Free Dietmentioning
confidence: 97%
“…GFD appears to lead to symptomatic improvement in these patients. To date, there is not enough evidence to recommend a GFD in IBD patients [24,25].…”
Section: Specific Carbohydrate Diet (Scd)mentioning
confidence: 99%
“…Among elimination diets, the gluten-free diet (GFD) has undoubtedly sparked interest. Indeed, a genetic predisposition for celiac disease may evoke the onset of IBD, although a causative relationship between celiac disease and IBD has never been fully established [ 96 , 97 ]. To date, despite some experimental data on animal models showing that gluten triggers intestinal inflammation and increases epithelial barrier permeability, no clinical trials have clearly indicated that a GFD has effects on CD.…”
Section: Diets For the Treatment Of Crohn’s Diseasementioning
confidence: 99%
“…Consumption of beer is toxic to celiac patients and could results into this autoimmune disorder due to the presence of gliadin from wheat gluten, prolamines/hordeins from barley, and secalins from rye [19,56]. Scientific research has shown that the successful long-term management of this autoimmune disorder is strict adherence to GF diets [57][58][59]. Hence, the needs for GF-beer.…”
Section: Gluten-free Beermentioning
confidence: 99%